Light Deprivation-Induced Inhibition of Chloroplast Biogenesis Does Not Arrest Embryo Morphogenesis But Strongly Reduces the Accumulation of Storage Reserves during Embryo Maturation in Arabidopsis - Liu, Huichao; Wang, Xiaoxia; Ren, Kaixuan; Li, Kai; Wei, Mengmeng; Wang, Wenjie; Sheng, Xianyong (Frontiers in Plant Science, 2017)
The chloroplast is one of the most important organelles found exclusively in plant and algal cells. Previous reports indicated that the chloroplast is involved in plant embryogenesis, but the role of the organelle during embryo morphogenesis and maturation is still a controversial question demanding further research. In the present study, siliques of Arabidopsis at the early globular stage were enwrapped using tinfoil, and light deprivation-induced inhibition of the chloroplast biogenesis were validated by stereomicroscope, laser scanning confocal microscope and transmission electron microscope. Besides, the effects of inhibited chloroplast differentiation on embryogenesis, especially on the reserve deposition were analyzed using periodic acid-Schiff (PAS) reaction, Nile red labeling, and Coomassie brilliant blue staining. Our results indicated that tinfoil enwrapping strongly inhibited the formation of chloroplasts, which did not arrest embryo morphogenesis, but markedly influenced embryo maturation, mainly through reducing the accumulation of storage reserves, especially starch grains and oil. Our data provide a new insight into the roles of the chloroplast during embryogenesis.